Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/jbm.a.35265
|View full text |Cite
|
Sign up to set email alerts
|

Poly (3‐hydroxybutyrate‐co‐3‐hydroxyhexanoate) scaffolds coated with PhaP‐RGD fusion protein promotes the proliferation and chondrogenic differentiation of human umbilical cord mesenchymal stem cells in vitro

Abstract: Human umbilical cord blood-derived mesenchymal stem cells (hUC-MSCs) have been widely used in tissue engineering. The aim of this study is to evaluate the ability of poly (3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBHHx) scaffolds coated with polyhydroxyalkanoate binding protein fused with arginyl-glycyl-aspartic acid (PhaP-RGD) to promote the proliferation and chondrogenic differentiation of hUC-MSCs seeded on them. The PhaP-RGD fusion protein was expressed by Escherichia coli. PHBHHx films were coated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The alternative studies led to isolation of MSCs from perinatal sources, which are more primitive, potent and proliferative, and can be acceptable for allogeneic and xenogeneic transplantation studies (Beeravolu et al ., ; Rachakatla et al ., ; Weiss and Troyer, ). Consequently, several reports have indicated that perinatal MSCs have the potential to produce ECM which is an integral component of NP of the IVD (Anderson et al ., ; Chon et al ., ; Ibrahim et al ., ; Li et al ., , ).…”
Section: Discussionmentioning
confidence: 99%
“…The alternative studies led to isolation of MSCs from perinatal sources, which are more primitive, potent and proliferative, and can be acceptable for allogeneic and xenogeneic transplantation studies (Beeravolu et al ., ; Rachakatla et al ., ; Weiss and Troyer, ). Consequently, several reports have indicated that perinatal MSCs have the potential to produce ECM which is an integral component of NP of the IVD (Anderson et al ., ; Chon et al ., ; Ibrahim et al ., ; Li et al ., , ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of matrix scaffolds is a key component in the success of cartilage engineering. A number of recent studies have shown that UCB-MSCs are able to differentiate into chondrocytes in scaffolds454647. For example, equine UCB-MSCs in membrane culture at low oxygen tension in the presence of TGF-β3 (10 ng/ml) produce a comparatively larger amount of high-quality neo-cartilage in comparison with differentiated cells in the pellet model46.…”
Section: Discussionmentioning
confidence: 99%
“…The pluripotent stem cells surface markers express in hUC-MSCs including Oct-4, Sox-2 [36] . hUC-MSCs have the potential of multidirectional differentiation, and which can differentiate into chondrocytes [37] , hepatocytes [38] , and adipocytes [39] . The cells we obtained from umbilical cord express CD90 (99.16% ± 0.85%) and CD105 (99.26% ± 0.78%), but no expression of CD34 (0.59% ± 0.16%) and CD45 (1.50% ± 2.04%) by these cells and 66.57% ± 4.61% cells expressed positively Oct-4 analyzed by ow cytometry.…”
Section: Discussionmentioning
confidence: 99%